2010
DOI: 10.1051/radiopro/2010028
|View full text |Cite
|
Sign up to set email alerts
|

Radioactivity concentrations and dose assessment for bitumen and soil samples around a bituminous deposit in Ondo State, Nigeria

Abstract: Bitumen samples and soil samples around a bituminous deposit in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
(9 reference statements)
1
5
1
Order By: Relevance
“…The mean activity concentrations recorded in the present study were also compared with the World Health Organization (WHO,1996) guideline values of activity concentration for radionuclides in drinking water. The Comparison of the results obtained in the mining sites with published data from similar investigations in other parts of the country and the world average was presented in Lower activity concentration was observed by Ademola and Ademonehin (2010), Innocent et al (2013); in Nigeria, Faanu et al (2011) in Ghana, Berekta and Mathew (1985) in Australia, Amrani and Tahbat (2001) in Algeria for 238 U compared with this study. In other hand, the result obtained in this study was also lower than the values reported by Ademola and Obed (2012) in Nigeria, Berekta and Mathew (1985) in Australia, Amrani andTahbat (2001) in Algeria, Manlancaet al, (1993) in brazil and in Egypt (El Afifi et al, 2006).…”
Section: Figure1: Activity Concentration For 238 U 232 Th and 40 K Isupporting
confidence: 73%
See 1 more Smart Citation
“…The mean activity concentrations recorded in the present study were also compared with the World Health Organization (WHO,1996) guideline values of activity concentration for radionuclides in drinking water. The Comparison of the results obtained in the mining sites with published data from similar investigations in other parts of the country and the world average was presented in Lower activity concentration was observed by Ademola and Ademonehin (2010), Innocent et al (2013); in Nigeria, Faanu et al (2011) in Ghana, Berekta and Mathew (1985) in Australia, Amrani and Tahbat (2001) in Algeria for 238 U compared with this study. In other hand, the result obtained in this study was also lower than the values reported by Ademola and Obed (2012) in Nigeria, Berekta and Mathew (1985) in Australia, Amrani andTahbat (2001) in Algeria, Manlancaet al, (1993) in brazil and in Egypt (El Afifi et al, 2006).…”
Section: Figure1: Activity Concentration For 238 U 232 Th and 40 K Isupporting
confidence: 73%
“…In other hand, the result obtained in this study was also lower than the values reported by Ademola and Obed (2012) in Nigeria, Berekta and Mathew (1985) in Australia, Amrani andTahbat (2001) in Algeria, Manlancaet al, (1993) in brazil and in Egypt (El Afifi et al, 2006). The average activity concentration of 232 Th obtained in this study was also lower than that obtained in Nigeria by Ademola and Ademonehin (2010) as well as Innocent et al (2013), Amrani and Tahbat (2001) in Algeria, Berekta and Mathew (1985) in Australia, El Afifi et al (2006) in Egypt and Manlanca et al (1993) in brazil but higher than the result obtained by Ademola and Obed (2012).…”
Section: Figure1: Activity Concentration For 238 U 232 Th and 40 K Icontrasting
confidence: 59%
“…The index I γr estimated is 0.7, which is less than unity. (Obed et al, 2005;Ademola et al, 2010). The calculated mean absorbed dose rate in air was 47.6 ± 7.7 nGy h -1 .…”
Section: Radium Equivalent Internal Hazard External Hazard and Gammmentioning
confidence: 90%
“…This study covers the Abakaliki metropolis ( Figure 2) which is the capital of the Ebonyi state Nigeria. It is located on latitude 06°15' N and 06°25' N and longitude of 08°00' E and 08°10' E and covers about 420 km 2 The administrative status, the academic activities and fertile agricultural soil of the surrounding towns are the most significant reasons for the rapid economic growth in population and the spatial expansion of the metropolis. The climate of the study area is that of tropical rainforest with distinct wet and dry seasons.…”
Section: Description Of the Area And Geological Settingmentioning
confidence: 99%
“…According to UNSCEAR (7), inhalation of radon decay products in quarry sites can lead to high incidences of lung cancer in mine workers. Although there have been extensive studies on the radionuclide concentrations (1,2) in Nigerian mines, radionuclide concentrations have not been subjected to radiological regulatory control and so there is little or no awareness of the radiological hazards on the exposure to NORMs in mining areas such as in the Abakaliki area. Due to the health risks associated with the exposure to NORMs and inhalation of the short-lived decay products of radon, international bodies such as International Commission on Radiological Protection and Environmental Protection Agency (4) adopted strong measures at minimizing risk to such exposure.…”
mentioning
confidence: 99%